2009
DOI: 10.1016/j.joca.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in spatial collagen content and collagen network architecture in porcine articular cartilage during growth and maturation

Abstract: The present study revealed dynamic changes of the collagen network during growth and maturation of the pigs. The structure of the collagen network of young pigs gradually approached a network with the classical Benninghoff architecture. The probable explanation for the alterations is growth of the bone epiphysis with simultaneous adaptation of the cartilage to increased joint loading. The maturation of articular cartilage advances gradually with age and offers, in principle, the possibility to influence the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
115
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 40 publications
19
115
2
Order By: Relevance
“…The data on porcine AC by Rieppo et al also shows some evidence for a valley in collagen density near the articular surface for the youngest age group, but not for the older age groups [21, figure 2a]. Similarly, we find strong evidence for a valley in collagen density in the youngest animals that disappears with increasing age (table 4, figure 5c).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The data on porcine AC by Rieppo et al also shows some evidence for a valley in collagen density near the articular surface for the youngest age group, but not for the older age groups [21, figure 2a]. Similarly, we find strong evidence for a valley in collagen density in the youngest animals that disappears with increasing age (table 4, figure 5c).…”
Section: Discussionsupporting
confidence: 80%
“…Rieppo et al [21] looked at domestic pig AC from the femoral groove at 4 months, 11 months and 21 months of age. As in our study, they found that collagen density shows a maximum between the superficial and deep zone in the youngest age group, and that collagen density increases monotonically between the superficial and the deep zone for the oldest animals [21, figure 4a].…”
Section: Discussionmentioning
confidence: 99%
“…Articular cartilage is a multiphasic tissue, the solid phase of which is composed predominately of a collagen (mainly type II) fibrillar network (around 10-22% by wet weight) enmeshing proteoglycan macromolecules (2-7% by wet weight) (Maroudas et al, 1969;Muir et al, 1970;Bayliss and Ali, 1978;Inerot et al, 1978;Maroudas et al, 1980;Zirn et al, 1984;Mow et al, 1992;Rieppo et al, 2009;Gannon et al, 2012). Previous studies have demonstrated that the application of dynamic compression (Huang et al, 2010;Bian et al, 2012;Thorpe et al, 2013) or hydrostatic pressure (Miyanishi et al, 2006;Wagner et al, 2008;Ogawa et al, 2009;Huang et al, 2010;Meyer et al, 2011;Correia et al, 2012;Liu et al, 2012;Steward et al, 2012;Vinardell et al, 2012a;Liu et al, 2013) can enhance the sGAG and collagen content as well as the mechanical functionality of cartilage constructs engineered using MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular specificity of the univariate parameters for collagen and proteoglycans in human AC has been questioned because of the overlap between the absorption peaks (33). Enzymatic removal of proteoglycans can be used before conducting the measurements to increase the specificity of amide I parameter for collagen (34)(35)(36).…”
Section: ¡1mentioning
confidence: 99%